Local Wisdom in Indonesian Language Textbooks for Elementary School in Lebak District - Siti Maemunah (IJECA (International Journal of Education and Curriculum Application), 2026)
This study highlights the importance of Indonesian language education in elementary schools as a foundation for developing students’ communication skills while emphasizing the need to integrate local wisdom into learning practices. The research is significant because many textbooks still prioritize standardized content and pay limited attention to students’ sociocultural backgrounds. Therefore, the study aims to examine the representation of local wisdom in Indonesian language textbooks used in primary schools in Lebak Regency and to explore how teachers utilize cultural elements in classroom learning. A qualitative approach was employed, using document analysis and classroom observation to understand both the written content of textbooks and its pedagogical implementation. The findings reveal that local wisdom is only minimally represented and often appears as additional examples rather than as a structured instructional framework. As a result, teachers play a central role in contextualizing lessons by incorporating local narratives and culturally relevant materials that reflect students’ everyday experiences, although they face challenges such as limited access to authentic resources and curriculum demands aligned with national and global standards. The study implies that stronger collaboration among local governments, educational institutions, and community stakeholders is essential to support culturally responsive learning. Integrating local wisdom more systematically can enhance student engagement, strengthen cultural awareness, and promote inclusive and meaningful language learning that aligns with global educational perspectives.